High-speed complex field modulation using binary phase-engraved superpixels - Patrick Kilcullen; Jingdan Liu; Youmin Wang; Lei Gong; Jinyang Liang (Light: Advanced Manufacturing)
Complex field modulation (CFM) has found a plethora of applications in physics, biomedicine, and instrumentation. Among existing methods, superpixel-based CFM has been increasingly featured because of its advantages in high modulation accuracy and its compatibility with high-speed spatial light modulators (SLMs). Nonetheless, the mainstream approach based on binary-amplitude modulation confronts limitations in optical efficiency and dynamic range. To surmount these challenges, we develop binary phase-engraved (BiPE) superpixel-based CFM and implement it using the phase light modulator (PLM)—a new micro-electromechanical system-based SLM undergoing development by Texas Instruments in recent years. Using BiPE superpixels, we demonstrate high-accuracy spatial amplitude and phase modulation at up to 1.44 kHz. To showcase its broad utility, we apply BiPE-superpixel-based CFM to beam shaping, high-speed projection, and augmented-reality display.